Economic growth and sustainable employment generation: Empirical validation of Okun’s law in Nigeria - Ayinde, Taofeek Olusola; Adekunle, Oluwatobi Ahmed; Muritala, Adewale Taiwo (Journal of Management, Economics, and Industrial Organization, 2018)
This study harps on the Okun’s law to examine the patterns of economic growth in Nigeria. The study employs an augmented employment demand equation and time-series data 1980-2015. The multivariate regression techniques were used for the study. Given a one-to-one relation, our results confirm the Okun’s (1962) propositions between the growth rate and the level of employment with 0.317 elasticities. Introducing other control variables to align with reality, the R-squared indicates that real GDP accounts for 78 percent movement in the level of employment in the country. It is evident that Nigerian economy is tending towards a service driven economy with much drive from the infrastructural development. For government to reduce the level of unemployment, focus must be placed on both the population growth and compensation to workers in the country, the growth should be made sectoral enterprising that both the industrial and agricultural sector will serve as the sine qua non of inclusive growth in Nigeria.